On the Way to Empire? - Engels, David (Humaniora. Czasopismo Internetowe, 2020)
The parallels between the crisis of the modern West and the fall of the Roman Republic in the 1st century BC are staggering: mass immigration, shrinking demography, decline of the family, erosion of the traditional religion, globalisation, social polarisation, a culture of bread and circuses, debt crisis, technocracy, asymmetrical wars, populism, etc. The present paper tries to summarise these analogies and reflects on the possibility of seing the West suffer similar events than those affecting the late Republic: civil unrest, rise of charismatic individuals, instauration of an authoritarian State.